The diversity, metabolomics profiling, and the pharmacological potential of actinomycetes isolated from the estremadura spur pockmarks (Portugal) - Pinto-Almeida, António (2021)
LA/P/0140/2020 PTDC/QUIQUI/119116/2010 Decree-Law 57/2016, of 29 August, changed by Law 57/2017, of 19 July.